2014
DOI: 10.9790/5736-0752119122
|View full text |Cite
|
Sign up to set email alerts
|

Association of Serum Adiponectin with Serum Insulin and Body mass density (BMD) in postmenopausal Osteoporotic women with and without T2DM

Abstract: B(r = 0.419,p = 0.021).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Recent years have witnessed great interest in diabetes and its complications. More recently, the association between diabetes and periodontitis has been investigated [1][2][3] ,as studies have shown that patients with high blood sugar suffer from persistent inflammation, and many studies were conducted previously, including diabetic kidney disorders .A phenomenon known as diabetic kidney disease (DKD) is characterized by alterations in the glomerular filtration rate, leakage of protein (particularly albumin), metabolites, and ions into the urine (GFR) [4][5][6][7] , diabetic neuropathies previous studies found that about half of diabetic patients have neuropathy, which consists of weakness in the peripheral nerves and may occur in various ways, including sensory, focal/multifocal, and autonomic neuropathy [8][9][10][11] , and the relationship between diabetes and osteoporosis increases blood sugar and decreases insulin secretion leading to an increase in susceptibility to osteoporosis [12][13][14] , in addition to a number of other studies in the field of diabetes treatments in which blood sugar was naturally controlled in patients with type 2 diabetes 15,16. Diabetic kidney disease is an illness of the glomerulus that interferes with the glomerular filtration barrier (GFB). It works in tandem to enable water and solutes to be selectively purified, while limiting the movement of large macromolecules such as albumin 17 .…”
Section: Introductionmentioning
confidence: 99%
“…Recent years have witnessed great interest in diabetes and its complications. More recently, the association between diabetes and periodontitis has been investigated [1][2][3] ,as studies have shown that patients with high blood sugar suffer from persistent inflammation, and many studies were conducted previously, including diabetic kidney disorders .A phenomenon known as diabetic kidney disease (DKD) is characterized by alterations in the glomerular filtration rate, leakage of protein (particularly albumin), metabolites, and ions into the urine (GFR) [4][5][6][7] , diabetic neuropathies previous studies found that about half of diabetic patients have neuropathy, which consists of weakness in the peripheral nerves and may occur in various ways, including sensory, focal/multifocal, and autonomic neuropathy [8][9][10][11] , and the relationship between diabetes and osteoporosis increases blood sugar and decreases insulin secretion leading to an increase in susceptibility to osteoporosis [12][13][14] , in addition to a number of other studies in the field of diabetes treatments in which blood sugar was naturally controlled in patients with type 2 diabetes 15,16. Diabetic kidney disease is an illness of the glomerulus that interferes with the glomerular filtration barrier (GFB). It works in tandem to enable water and solutes to be selectively purified, while limiting the movement of large macromolecules such as albumin 17 .…”
Section: Introductionmentioning
confidence: 99%